Carbon Budget of Tidal Wetlands, Estuaries, and Shelf Waters of Eastern North America. Issue 3 (11th March 2018) - Najjar, R. G.; Herrmann, M.; Alexander, R.; Boyer, E. W.; Burdige, D. J.; Butman, D.; Cai, W.‐J.; Canuel, E. A.; Chen, R. F.; Friedrichs, M. A. M.; Feagin, R. A.; Griffith, P. C.; et al.
Abstract: Carbon cycling in the coastal zone affects global carbon budgets and is critical for understanding the urgent issues of hypoxia, acidification, and tidal wetland loss. However, there are no regional carbon budgets spanning the three main ecosystems in coastal waters: tidal wetlands, estuaries, and shelf waters. Here we construct such a budget for eastern North America using historical data, empirical models, remote sensing algorithms, and process‐based models. Considering the net fluxes of total carbon at the domain boundaries, 59 ± 12% (± 2 standard errors) of the carbon entering is from rivers and 41 ± 12% is from the atmosphere, while 80 ± 9% of the carbon leaving is exported to the open ocean and 20 ± 9% is buried. Net lateral carbon transfers between the three main ecosystem types are comparable to fluxes at the domain boundaries. Each ecosystem type contributes substantially to exchange with the atmosphere, with CO2 uptake split evenly between tidal wetlands and shelf waters, and estuarine CO2 outgassing offsetting half of the uptake. Similarly, burial is about equal in tidal wetlands and shelf waters, while estuaries play a smaller but still substantial role. The importance of tidal wetlands and estuaries in the overall budget is remarkable given that they, respectively, make up only 2.4 and 8.9% of the study domain area. This study shows that coastal carbon budgets should explicitly include tidal wetlands, estuaries, shelf waters, and the linkages between them; ignoring any of them may produce a biased picture of coastal carbon cycling. Plain Language Summary: A carbon budget for a particular site or region describes the inputs and outputs of carbon to that site or region as well as the processes that change carbon from one form to another. A carbon budget is needed to fully understand many important issues facing coastal waters. We constructed the carbon budget for coastal waters of eastern North America. We found that about 60% of the carbon entering the domain is from rivers and about 40% is from the atmosphere, while about 80% of the carbon leaving the domain goes to the open ocean and about 20% is buried. Transfers of carbon from wetlands to estuaries and from estuaries to the ocean were as important as transfers of carbon at the domain boundaries. Tidal wetlands and estuaries were found to be important to the carbon budget despite making up only 2.4 and 8.9% of the study domain area, respectively. This study shows that coastal carbon budgets should explicitly consider tidal wetlands, estuaries, shelf waters, and the linkages between them; ignoring any of them may produce a biased picture of coastal carbon cycling. Key Points: Tidal wetlands, estuaries, and shelf waters each contribute substantially to the carbon budget of eastern North American coastal waters Study region net ecosystem production, atmospheric uptake, and burial are 20.2 ± 4.4, 5.1 ± 2.4, and 2.5 ± 0.7 Tg C yr −1, respectively Net lateral carbon fluxes between tidal wetlands, estuaries, and shelf waters are large terms in the carbon budget of eastern North American coastal waters